2004
DOI: 10.1164/rccm.200208-960oc
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Exacerbations after Glucocorticoid Withdrawal Reflects T Cell Recruitment to the Airway

Abstract: We reasoned that a prospective assessment of glucocorticoid withdrawal in subjects with asthma would provide insight into the basis for flares of the disease. We therefore enrolled 25 subjects with moderate persistent asthma and treated them for 30 days with inhaled fluticasone propionate (1,760 microg/day) followed by a withdrawal period that lasted until peak expiratory airflow decreased by 25% and FEV(1) by 15% or 6 weeks elapsed. After glucocorticoid withdrawal, 13 of 25 subjects reached the target, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 58 publications
3
36
1
Order By: Relevance
“…In the study of Pizzichini et al (66) sputum eosinophil counts were raised several weeks before the increase in symptoms and reduction in FEV 1 . Likewise, Castro et al (67) showed that progressive withdrawal of inhaled corticosteroids led to an increase in bronchial eosinophilia and bronchial infiltration by T-cells (CD8+ or CD4+) associated with occurrence of an exacerbation.…”
Section: Causes Of Exacerbationsmentioning
confidence: 97%
“…In the study of Pizzichini et al (66) sputum eosinophil counts were raised several weeks before the increase in symptoms and reduction in FEV 1 . Likewise, Castro et al (67) showed that progressive withdrawal of inhaled corticosteroids led to an increase in bronchial eosinophilia and bronchial infiltration by T-cells (CD8+ or CD4+) associated with occurrence of an exacerbation.…”
Section: Causes Of Exacerbationsmentioning
confidence: 97%
“…Isotype control Abs were used as negative controls. Grading was performed as previously described (9). Differences in immunohistochemical staining was quantified (for Rb and Bcl-2) as previously described (24,25).…”
Section: Immunohistochemistry and Tunel Analysismentioning
confidence: 99%
“…Previously, we have shown that airway epithelial cells provide critical signals for epithelial-immune cell interaction resulting in airway inflammation and remodeling (9)(10)(11)(12). We hypothesized that cellular proliferation and cell death of airway epithelial cells may explain, at least in part, the structural remodeling changes noted in severe asthma.…”
mentioning
confidence: 99%
“…There are short-and long-term measures of asthma control (12,13). Short-term measures include the assessment of measures of airway inflammation and composite measures of asthma control such as the Asthma Control Questionnaire (ACQ).…”
Section: Assessment Of Asthma Control and Questionnairesmentioning
confidence: 99%